2019
DOI: 10.3389/fpsyt.2019.00170
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation in Youth With Treatment Resistant Major Depression

Abstract: Background: Major depressive disorder (MDD) is common in youth and treatment options are limited. We evaluated the effectiveness and safety of repetitive transcranial magnetic stimulation (rTMS) in adolescents and transitional aged youth with treatment resistant MDD. Methods: Thirty-two outpatients with moderate to severe, treatment-resistant MDD, aged 13–21 years underwent a three-week, open-label, single center trial of rTMS (ClinicalTrials.gov identifier NCT01731678). rTMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
1
39
0
1
Order By: Relevance
“…Tables 1 and 2 summarized the characteristics of the studies. The studies include open-label trials [27][28][29][30][31][32], case reports [33][34][35][36][37], case series [38][39][40][41], naturalistic studies [42], and randomized sham-controlled trial [43].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 summarized the characteristics of the studies. The studies include open-label trials [27][28][29][30][31][32], case reports [33][34][35][36][37], case series [38][39][40][41], naturalistic studies [42], and randomized sham-controlled trial [43].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The majority of the studies are from the USA [28][29][30][31][33][34][35]40,43]. The rest of the studies were from China [37,38,42], Israel [32], Finland [36], Canada [27,39], Australia [41], and across multiple nations [44]. The lowest age of the recipient of rTMS was ten [40,42,43], but most of the patients were above 12.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Meta‐analysis of adult studies suggests that at the end of an acute treatment series the risk ratios for a treatment response are 1.72 (95% CI: 1.13–2.62) with a small effect size of 0.33 (95% CI 0.17–0.50) compared with sham treatment (Ontario, ). Uncontrolled studies of rTMS in adolescent depression have suggested possible efficacy and safety of rTMS (Bloch et al, ; Croarkin et al, ; MacMaster et al, ), but there are no controlled trials. Side effects of rTMS in pediatric patients appear similar to adults and include headache, scalp pain, and rare seizures (Magavi, Reti, & Vasa, ).…”
Section: Strategies For Treatment‐resistant Depressionmentioning
confidence: 99%
“…In Alberta, a publicly funded service was first opened in Ponoka in 2004 and a private clinic was added in Calgary in 2012. In 2013, research began in earnest in Alberta at the Alberta Children's Hospital and the University of Calgary to evaluate TMS as a treatment for youth with depression (20). The research involved in that open-label trial (NCT01731678) (20) provided first-hand experience and data on patient outcomes and the safety, tolerability, and acceptability of TMS as a treatment for depression in youth.…”
Section: History Of Tms In Albertamentioning
confidence: 99%
“…In 2013, research began in earnest in Alberta at the Alberta Children's Hospital and the University of Calgary to evaluate TMS as a treatment for youth with depression (20). The research involved in that open-label trial (NCT01731678) (20) provided first-hand experience and data on patient outcomes and the safety, tolerability, and acceptability of TMS as a treatment for depression in youth. This work, combined with the clinical work in Ponoka, were the critical first steps in developing a plan to create a TMS clinical service for treatment of depression in Alberta.…”
Section: History Of Tms In Albertamentioning
confidence: 99%